Natural Disaster and Heritage Tourism: A Study on the Impacts of Earthquake in Bhaktapur, Nepal - Kunwar, Ramesh Raj; Chand, Usha (Journal of Tourism and Hospitality Education, 2016)
The article reviews on the complex and intricate linkages between heritage and tourism, highlighting the importance of the heritage industry and the vulnerability the industry can face when confronted with a natural disaster such as earthquake. The article aims not just to introduce the Kathmandu Valley in the light of the seven World Heritage Sites but also aims to prioritize the devastation that the recent earthquake brought upon the ‘Living Heritage’, Bhaktapur. The article assesses the earthquake’s impact on tourism in Bhaktapur and finally sheds light upon the tourism recovery process that is undergoing along with the issues of heritage reconstruction with a comparison on what has been done and what has to be done for the overall purpose of tourism recovery.Journal of Tourism and Hospitality Education (Vol. 6), 2016, Pages: 1-39